Concept of a thin film memory transistor based on ZnO nanoparticles insulated by a ligand shell - Hirschmann, Johannes; Faber, Hendrik; Halik, Marcus (Nanoscale, 2012)

Conductance Enhancement of Nano-Particulate Indium Tin Oxide Layers Fabricated by Printing Technique - Groß, Michael; Maksimenko, Ilja; Faber, Hendrik; Linse, N.; Wellmann, Peter (Nanotech 2008, Vol. 1-3, 2008)
To understand the mechanisms behind the conductance improvement and to fathom the limits we did some investigations: long-term resistance measurements gave an insight in oxygen vacancy balance concentration. From infrared absorption measurements we inferred the free charge carrier density and at present we carry out XPS measurements which yield information about the alteration of oxygen vacancy concentration. Considering these data we discuss two conductance improving mechanisms: The increase of the free charge carrier density by a rise of oxygen vacancy concentration as well as a release of trapped charge carriers from the aggregate surface
Keywords: ITO; nanoparticles; transmittance; conductance

Fully Patterned Low-Voltage Transparent Metal Oxide Transistors Deposited Solely by Chemical Spray Pyrolysis - Faber, Hendrik; Butz, Benjamin; Dieker, Christel; Spiecker, Erdmann; Halik, Marcus (Advanced Functional Materials, 2013)
All-inorganic transparent thin-film transistors deposited solely by the solution processing method of spray pyrolysis are reported. Different precursor materials are employed to create conducting and semiconducting species of ZnO acting as electrodes and active channel material, respectively, as well as zirconium oxide as gate dielectric layer. Additionally, a simple stencil mask system provides sufficient resolution to realize the necessary geometric patterns. As a result, fully functional low-voltage n-type transistors with a mobility of 0.18 cm2 V−1 s−1 can be demonstrated via a technique that bears the potential for upscaling. A detailed microscopic evaluation of the channel region by electron diffraction, high-resolution and analytical TEM confirms the layer stacking and provides detailed information on the chemical composition and nanocrystalline nature of the individual layers.

Impact of oxygen plasma treatment on the device performance of zinc oxide nanoparticle based thin-film transistors - Halik, Marcus; Peukert, Wolfgang; Braunschweig, Björn; Klaumünzer, Martin; Hirschmann, Johannes; Faber, Hendrik (ACS Applied Materials and Interfaces, 2012)
Thin-films of zinc oxide nanoparticles were investigated by photoluminescence spectroscopy and a broad defect-related yellow-green emission was observed. Oxygen plasma treatment was applied in order to reduce the number of defects, and the emission intensity was quenched to 4% of the initial value. Thin-film transistors that incorporate the nanoparticles as active semiconducting layers show an improved device performance after oxygen plasma treatment. The maximum drain current and the charge carrier mobility increased more than 1 order of magnitude up to a nominal value of 23 cm2 V−1 s−1 and the threshold voltage was lowered.
Keywords: nanoparticles; Plasma treatment; thin-film transistors; zinc oxide

Influence of self-assembled monolayer dielectrics on the morphology and performance of α,ω-dihexylquaterthiophene in thin film transistors - Novak, Michael; Schmaltz, Thomas; Faber, Hendrik; Halik, Marcus (Applied Physics Letters, 2011)
Three different ultrathin hybrid dielectrics based on self-assembled monolayers (SAMs) from phosphonic acid molecules were investigated on aluminum oxide. The impact of the underlying SAMs on the semiconductor morphology and transistor device performance was studied by reducing the film thickness of the subsequently deposited extgreeka, extgreekw-dihexylquaterthiophene semiconductor to one monolayer and less. The nature of the SAM relates to the molecular orientation of submonolayer films, which is investigated by photoluminescence microscopy and atomic force microscopy. SAMs with high surface energy tend to induce a face-on growing of the semiconductor, whereas for SAMs with low surface energy an edge-on growth is favorable.
EAM Import::2019-03-14

Low-temperature solution-processed memory transistors based on zinc oxide nanoparticles - Faber, Hendrik; Burkhardt, Martin; Jedaa, Abdesselam; Kälblein, D.; Klauk, Hagen; Halik, Marcus (Advanced Materials, 2009)
We report on thin!film transistors based on ZnO nanoparticles processed from solution and with a maximum temperature of 100 °C. Electron mobilities up to 2.5 cm²V−1s−1 are obtained, and top-gate TFTs show non-volatile memory properties with a large, stable hysteresis and a memory ratio of 105. Memory TFTs operate in ambient, have good shelf-life (>6 months), and useful endurance properties.

Morphological impact of zinc oxide layers on the device performance in thin-film transistors - Faber, Hendrik; Klaumünzer, Martin; Voigt, Michael; Galli, Diana; Vieweg, Benito; Peukert, Wolfgang; Spiecker, Erdmann; Halik, Marcus (Nanoscale, 2011)
Zinc oxide thin-films are prepared either by spin coating of an ethanolic dispersion of nanoparticles (NP, diameter 5 nm) or by spray pyrolysis of a zinc acetate dihydrate precursor. High-resolution electron microscopy studies reveal a monolayer of particles for the low temperature spin coating approach and larger crystalline domains of more than 30 nm for the spray pyrolysis technique. Thin-film transistor devices (TFTs) based on spray pyrolysis films exhibit higher electron mobilities of up to 24 cm² V−1 s−1 compared to 0.6 cm² V−1 s−1 for NP based TFTs. These observations were dedicated to a reduced number of grain boundaries within the transistor channel.

Preparation and soft lithographic printing of nano-sized ITO-dispersions for the manufacture of electrodes for TFTs - Straue, Nadja; Rauscher, Martin; Walther, Sabine; Faber, Hendrik; Roosen, Andreas (Journal of Materials Science, 2009)